Mimosa scabrella BENTH. (FABACEAE) ENHANCES THE RESTORATION IN COAL MINING AREAS IN THE ATLANTIC RAINFOREST - Vanilde Citadini-Zanette (CERNE, 2017)
Pilot Reclamation Project (PRP) was developed in 1982 by the Environmental Protection Agency of the State of Santa Catarina-Brazil, with the objective to evaluating the adaptation of woody species to a land degraded by coal mining. After a full topographic reconstitution of the landscape, addition of nutrient load and sowing of herbaceous species, the area was split into 12 plots in which seedlings of 12 tree species were planted: three native trees [ Bastardiopsis densiflora (Hook. & Arn.) Hassl., Mimosa scabrella Benth., Schizolobium parahyba (Vell.) Blake] and nine exotic species [ Eucalyptus saligna Sm., E. viminalis Labill., E. citriodora Hook., Grevillea hilliana F.Muell., Hovenia dulcis Thunb, Melia azedarach L., Pinus elliottii Engelm., P. taeda L., Syzygium cumini (L.) Skeels]. After 22 years, from the beginning of the PRP, the exotic species presented higher percentage of survival than native species; the plots which received either B. densiflora and S. parahyba or were covered only with herbaceous vegetation associated with solely a few shrubs. Conversely, the plots which received seedlings of M. scabrella displayed clear evidence of restoration in progress. The study conducted in plots that have received M. scabrella indicate an improvement of nutrient load (N, K, organic matter) in the substrate, a diversified composition of tree coverage (very similar to the nearby remnants of the Atlantic Rainforest) and other life forms, with prominent establishment of native trees with predominance of zoophilous and zoochorous species. Some characteristics of M. scabrella that could explain its outstanding capacity to enhance the restoration of the Atlantic Rainforest are also discussed along this paper.